Adverse Childhood Experiences, Suicidal/Self-Harming Thoughts, and Suicide Attempts Among LGB and Heterosexual Utahns. Issue 7 (7th June 2022) - McGraw, James S.; McManimen, Stephanie; Chinn, Jessica; Angoff, Harrison D.; Docherty, Meagan; Mahoney, Annette
ABSTRACT: Current research suggests that sexual minorities living in Utah may be at higher risk for experiencing suicidal/self-harming thoughts and suicide attempts than heterosexuals in Utah. However, to date no research has been conducted examining potential reasons sexual minorities living in Utah may be at higher risk. Using two representative samples of Utahns, we examine (a) disparities in adverse childhood experiences (ACEs) between sexual minorities and heterosexual Utahn, (b) how ACEs and sexual orientation may predict recent suicidal/self-harming thoughts and lifetime prevalence of suicide attempts, and (c) how sexual orientation and ACEs might interact to predict suicidal outcomes. Results with each sample showed that sexual minority Utahns reported higher levels of ACEs and suicidal/self-harming thoughts than heterosexual Utahns. Both sexual orientation and ACEs uniquely predicted suicidality when both were entered into regression models, but no interaction effects were found between these predictors.